Fine structure and transcription dynamics of bread wheat ribosomal DNA loci deciphered by a multi-omics approach - Tulpová, Zuzana; Kovařík, Aleš; Toegelová, Helena; Navrátilová, Pavla; Kapustová, Veronika; Hřibová, Eva; Vrána, Jan; Macas, Jiří; Doležel, Jaroslav; Šimková, Hana (The plant genome, 2022)
Three out of four RNA components of ribosomes are encoded by 45S ribosomal DNA (rDNA) loci, which are organized as long head-to-tail tandem arrays of nearly identical units, spanning several megabases of sequence. Due to this structure, the rDNA loci are the major sources of gaps in genome assemblies, and gene copy number, sequence composition, and expression status of particular arrays remain elusive, especially in complex genomes harboring multiple loci. Here we conducted a multi-omics study to decipher the 45S rDNA loci in hexaploid bread wheat. Coupling chromosomal genomics with optical mapping, we reconstructed individual rDNA arrays, enabling locus-specific analyses of transcription activity and methylation status from RNA- and bisulfite-sequencing data. We estimated a total of 6,650 rDNA units in the bread wheat genome, with approximately 2,321, 3,910, 253, and 50 gene copies located in short arms of chromosomes 1B, 6B, 5D, and 1A, respectively. Only 1B and 6B loci contributed substantially to rRNA transcription at a roughly 2:1 ratio. The ratio varied among five tissues analyzed (embryo, coleoptile, root tip, primary leaf, mature leaf), being the highest (2.64:1) in mature leaf and lowest (1.72:1) in coleoptile. Cytosine methylation was considerably higher in CHG context in the silenced 5D locus as compared with the active 1B and 6B loci. In conclusion, a fine genomic organization and tissue-specific expression of rDNA loci were deciphered, for the first time, in a complex polyploid species. The results are discussed in the context of wheat evolution and transcription regulation.
Keywords: Triticum; Bread; ribozomální DNA; chléb; Polyploidy; DNA, Ribosomal; pšenice; RNA ribozomální; RNA, Ribosomal; polyploidie